The rise of commodity care - Jacy E. Neczypor; Jacy E. Neczypor; Jacy E. Neczypor (Frontiers in Health Services)
The commoditization of health care under the guise of advanced preventive services and data-driven performance optimization poses risks for patient care and lessons for health systems. This editorial defines and examines “commodity care,” a growing model of direct-to-consumer healthcare characterized by self-referral for advanced diagnostic imaging and/or serologic testing. Promoted as empowering and proactive preventive care, commodity care services frequently operate beyond established clinical guidelines and lack robust evidence to support their clinical utility. Despite appealing marketing claims, these services carry significant risks for patients, including overdiagnosis, false-positive results, and incidental findings that lead to unnecessary interventions that may cause physical, psychological, and financial harms. At the health system level, commodity care contributes to fragmented patient experiences, promotes low-value utilization of healthcare resources, and raises ethical and environmental concerns related to data stewardship and sustainability. Yet, the rising demand for these services also suggests a deeper dissatisfaction among patients with traditional care models, particularly around issues of access, responsiveness, and personalization. Whether driven primarily by shortcomings of conventional healthcare delivery or by shifting patient expectations, the expansion of commodity care warrants careful attention from clinicians, policymakers, and regulators. Defining commodity care is an imperative first step in understanding its implications. This editorial advocates for increased regulatory oversight and rigorous evaluation of emerging healthcare models that increasingly blur distinctions between clinical medicine and consumer-oriented services. Ultimately, the advancement of healthcare technology should support—not erode—the quality, value, and patient-centeredness of care.